Effect of homogeneous Fenton combined with electron transfer on the fate of inorganic chlorinated species in synthetic and reclaimed municipal wastewater. (20th February 2020) - Mousset, Emmanuel; Quackenbush, Lenna; Schondek, Christine; Gerardin-Vergne, Arthur; Pontvianne, Steve; Kmiotek, Stephen; Pons, Marie-Noëlle
Abstract: This study newly investigates in detail the fate of inorganic chlorinated species and potential interference with other inorganic compounds such as phosphate, inorganic carbon and nitrogenous species during the electro-Fenton treatment of synthetic and reclaimed wastewater. A mathematical model was proposed to validate reaction pathways and rate constants of chlorinated species. The comparison of modeling results with experimental data of both synthetic and real solutions was quite good, with root mean square error (RMSE) values less than 0.084. Upon further testing, the results also showed that adding carbonate, phosphate and inorganic nitrogen species did not affect the chlorate and volatile chlorinated species accumulation subsequent to the decay of chloride ions during electro-Fenton. The established pathway in both synthetic and real chlorinated matrices could help to understand and predict the concentration profiles of chlorinated species in wastewater when implementing such electrocatalysis as a complementary treatment. This work also highlights the need to take into account the management of chlorinated intermediates when implementing this technology at larger scale.